Postmodernism and education: What does it imply? - Suárez M., José Olimpo (Estudios de Filosofía, 1998)
For the author, Rorty pragmatism is another variation of that cultural change called "Posmodernism ". He identifies and criticises some Rortian statements about the meaning of philosophy and of critical thought after which he can face the questions J. Searle has posed about the possible irrationalism springing offer Posmodernism in education. Looking for a proper framework for this thesis, the author opposes two of the many meanings given to the term Posmodernism. He criticises the idea of setting epistemology as a nucleus to the tasks of Modernity for the Western. He then points out some concepts such as philosophy, reason, and education in Rorty's thesis. Education turns to be a quite ethic activity and not a new methodological skill as it was conceived in llustrated liberal education' and shared by Searle. The author also states that Posmodernism is not the realm of relativism not either of nonsense.